MODULAR DECISION SUPPORT SYSTEM DURING THE OPTIMIZATION OF RESOURCE DISTRIBUTION BETWEEN PROTECTED OBJECTS - Akhmetova, Б.C.; Adilzhanova, С.А.; Abuova, А.К.; Sagyndykova, Ш. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
The article proposes a block diagram of the functioning of the decision support system (DSS) in the process of analyzing and choosing a rational (optimal) variant of the strategy for allocating resources of the information security side at informatization facilities in conditions of dynamic confrontation with the opposing side (hacker). The key functional modules of such a DSS are considered, which contribute to ensuring the continuous and effective functioning of the system.